Redefining the draft pick valuation in the National Football League - Hadley, Bryce; Kim, Jun Woo; Magnusen, Marshall; Kim, Kyoung Tae (Frontiers in Sports and Active Living, 2025)
The National Football League (NFL) Draft plays a critical role in determining team compositions and enhancing the competitive balance within the league. This study examines the valuation dynamics of NFL Draft picks, contrasting traditional valuation paradigms like Jimmy Johnson's Pick Value Chart (PVC) to estimate the intrinsic value of draft selections. Utilizing metrics such as weighted approximate value (wAV), games played (GP), and seasons started (ST), we derived that late-round draft picks might be undervalued in the conventional PVC. Our regression results indicated that the final pick in the first round holds a value closer to 56% of the first pick's worth, contrasting sharply with PVC's 20%. Our refined model suggested that the value of a pick 200 is about 30 times more than what PVC projects. We incorporate round-specific “Traded Up” dummy variables into our player-level regression models to test whether trade-up selections yield better outcomes. Results reveal that early round trade-ups, particularly in Round 1, are associated with significantly lower player performance, suggesting inefficiencies driven by overconfidence. In contrast, trade-ups in Round 4 show a modest positive effect, while other rounds yield no consistent advantage. These findings indicate that teams may benefit more from accumulating late-round picks than from aggressively trading up early. This paper accentuates the need for NFL teams to integrate data-driven models for informed draft decisions, thereby deepening insights into NFL draft valuation.